A Corpus-Based Study on the Use of Spoken Discourse Markers by Thai EFL Learners - Pan, Zhaoyi; Aroonmanakun, Wirote (LEARN Journal: Language Education and Acquisition Research Network, 2022)
This research investigated the use of English spoken discourse markers by Thai EFL learners in English conversation compared to native English speakers from two perspectives: frequency and pragmatic function. A total of 60 learners were involved in the research: 30 Thai B1-level learners and 30 Thai C1-level EFL learners. Spoken data was collected and transcribed into written form to build a learner corpus for analysis. The data analysis indicated underuse by Thai EFL learners of four spoken discourse markers – so, well, you know and I think. Moreover, Thai EFL learners we shown to use each spoken discourse marker differently in comparison to native English speakers. On the whole, interpersonal functions were less frequently a factor than textual functions, indicating a larger deficiency in performing interpersonal functions by Thai EFL learners. These results lead to the conclusion that Thai EFL learners lack pragmatic competence in oral communication in terms of performance (usage instance) discrepancy regarding spoken discourse markers compared to native English speakers.